A post-translational modification of human Norovirus capsid protein attenuates glycan binding - Alvaro Mallagaray (Nature Portfolio, 2019)
Attachment of human noroviruses to histo blood group antigens (HBGAs) is essential for infection. Here the authors report that an asparagine residue located near the HBGA-attachment site can convert into an iso-aspartate residue through spontaneous deamidation and influence HBGA recognition.